Multifunctional reduced graphene oxide-CVD graphene core–shell fibers. Issue 26 (25th June 2019) - Choi, Yong Seok; Yeo, Chang-su; Kim, Sang Jin; Lee, Jin-Young; Kim, Youngsoo; Cho, Kang Rae; Ju, Sanghyun; Hong, Byung Hee; Park, Sang Yoon
Abstract : The graphene-based fiber structure with rGO cores and CVD graphene shells, showing an outstanding electrical conductivity and electrochemical performance with enhanced mechanical stability and durability. Abstract : The insufficient electrical conductivity and mechanical stretchability of conventional graphene fibers based on reduced graphene oxide liquid crystals (rGO-LCs) has limited their applications to numerous textile devices. Here, we report a simple method to fabricate multifunctional fibers with mechanically strong rGO cores and highly conductive CVD graphene shells (rGO@Gr fibers), which show an outstanding electrical conductivity as high as ∼137 S cm −1 and a failure strain value of 21%, which are believed to be the highest values among polymer-free graphene fibers. We also demonstrate the use of the rGO@Gr fibers for high power density supercapacitors with enhanced mechanical stability and durability, which would enable their practical applications in various smart wearable devices in the future.